An artificial neural network hybrid with wavelet transform for short-term wind speed forecasting: A preliminary case study - Yousefi M.; Hooshyar D.; Yousefi M.; Khaksar W.; Sahari K.S.M.; Alnaimi F.B.I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Big data; Feedforward neural networks; Forecasting; Neural networks; Signal processing; Speed; Statistical tests; Time series; Wind; Wind power; Auto-correlation factors; Forecasting accuracy; Forecasting performance; Inverse wavelet transforms; Neural network predictions; Short-term wind speed forecasting; Trial-and-error process; Wind speed forecasting; Wavelet transforms